Novel biocompatible magnetron-sputtered silver coating for enhanced antibacterial properties and osteogenesis in vitro - Talante Juma; Hongbin Wang; Xiangyu Cao; Qiwei Wang; Hao Wang; Bingxiao Yu; Xiaotong Bao; Wenjuan Rong; Hua Tian; Yongping Cao (Scientific Reports)
Abstract Peri-implant infection is a serious complication in orthopedic surgery. This study aimed to reduce the incidence of peri-implant infection by developing a durable and safe antibacterial silver coating. We compared the antibacterial properties and process controllability of various coating techniques to identify the most effective method for silver coating. We refined substrate treatment techniques and coating thicknesses through antibacterial and scratch tests. Scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS) were used to analyze the coating’s morphology and composition. Micron-sized magnetron sputtering silver coating samples underwent in vitro antibacterial testing, cytotoxicity testing, silver ion release testing, and osteogenic testing using membrane contact culture, CCK-8 assay, inductively coupled plasma (ICP) detection, and alkaline phosphatase (ALP) activity/osteogenic gene PCR. Magnetron sputtering demonstrated superior antibacterial properties, uniformity, and process controllability compared to alternative techniques. The optimal adhesion strength was achieved with a 0.5 μm coating thickness and a 400 mesh sandpaper pretreatment process, without compromising antibacterial efficacy. The coating showed near-perfect antiseptic results in antibacterial and anti-biofilm tests. Fibroblasts cultured in silver ion precipitation medium exhibited growth rates of 89% on day 30 and 88% on day 90, compared to 95% in the control group. The osteogenic test indicated that the magnetron sputtering silver coating promotes osteogenesis effectively. Our study demonstrated that micron-sized magnetron sputtering silver coating has potential for clinical use to prevent peri-implant infections in the future.